Effects of steam sterilization on reduction of fungal colony forming units, cannabinoids and terpene levels in medical cannabis inflorescences - Shachar Jerushalmi (Nature Portfolio, 2021)
Abstract Medical cannabis (MC) production is a rapidly expanding industry. Over the past ten years, many additional phytocannabinoids have been discovered and used for different purposes. MC was reported beneficial for the treatment of a variety of clinical conditions such as analgesia, multiple sclerosis, spinal cord injuries, Tourette's syndrome, epilepsy, glaucoma, Parkinson disease and more. Yet, there is still a major lack of research and knowledge related to MC plant diseases, both at the pre- and postharvest stages. Many of the fungi that infect MC, such as Aspergillus and Penicillium spp., are capable of producing mycotoxins that are carcinogenic, or otherwise harmful when consumed, and especially by those patients who suffer from a weakened immune system, causing invasive contamination in humans. Therefore, there are strict limits regarding the permitted levels of fungal colony forming units (CFU) in commercial MC inflorescences. Furthermore, the strict regulation on pesticide appliance application in MC cultivation exacerbates the problem. In order to meet the permitted CFU limit levels, there is a need for pesticide-free postharvest treatments relying on natural non-chemical methods. Thus, a decontamination approach is required that will not damage or significantly alter the chemical composition of the plant product. In this research, a new method for sterilization of MC inflorescences for reduction of fungal contaminantstes was assessed, without affecting the composition of plant secondary metabolites. Inflorescences were exposed to short pulses of steam (10, 15 and 20 s exposure) and CFU levels and plant chemical compositions, pre- and post-treatment, were evaluated. Steam treatments were very effective in reducing fungal colonization to below detection limits. The effect of these treatments on terpene profiles was minor, resulting mainly in the detection of certain terpenes that were not present in the untreated control. Steaming decreased cannabinoid concentrations as the treatment prolonged, although insignificantly. These results indicate that the steam sterilization method at the tested exposure periods was very effective in reducing CFU levels while preserving the initial molecular biochemical composition of the treated inflorescences.